2 - The Silences in the NGO Discourse: The role and future of NGOs in Africa* - Shivji, Issa G. (Africa Development, 2006)
This paper is an attempt to examine critically the role and future of the NGO in Africa in the light of its self-perception as a non-governmental, non-political, non-partisan, non-ideological, non-academic, non-theoretical, not-for-profit as- sociation of well-intentioned individuals dedicated to changing the world to make it a better place for the poor, the marginalised and the downcast. It is the argument of the paper that the role of NGOs in Africa cannot be understood without a clear characterisation of the current historical moment. On a canvas of broad strokes, I depict Africa at the cross-roads of the defeat of the National Project and the rehabilitation of the imperial project. In the face of the avalanche of ‘end of history’ diatribes, I find it necessary, albeit briefly, to reiterate the history of Africa’s enslavement from the first contacts with the Europeans five centuries ago through the slave trade to colonialism and now globalisation. The aim of this historical detour is to demonstrate the fundamen- tal antithesis between the National and the Imperial Projects so as to identify correctly the place and role of the NGOs in it. I locate the rise, the prominence and the privileging of the NGO sector in the womb of the neo-liberal offensive whose aim is as much ideological as economic and political. I argue that the NGO discourse, or more correctly the non-dis- course, is predicated on the philosophical and political premises of neo-liberal- ism/globalisation paradigm. It is in this context that I go on to discuss the ‘five silences’ or blind-spots in the NGO discourse. I draw out the implications of these silences on the contemporary and future role of the NGO sector in Africa.At the outset, I must make two confessions. First, the paper is undoubtedly critical, sometimes ruthlessly so, but not cynical. Secondly, the criticism is also a self-criticism since the author has been involved in NGO activism for the last fifteen years or so. And, finally, I must make it clear that I do not doubt the noble motivations and the good intentions of NGO leaders and activists. But one does not judge the outcome of a process by the intentions of its authors; one analyses the objective effect of actions regardless of intentions. Hopefully, that is what I have done.